2009
DOI: 10.1002/hbm.20523
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of laterality of verbal and visuospatial functions during childhood and adolescence

Abstract: Cognitive functions in the child's brain develop in the context of complex adaptive processes, determined by genetic and environmental factors. Little is known about the cerebral representation of cognitive functions during development. In particular, knowledge about the development of right hemispheric (RH) functions is scarce. Considering the dynamics of brain development, localization and lateralization of cognitive functions must be expected to change with age. Twenty healthy subjects (8.6-20.5 years) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
141
3
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 42 publications
13
141
3
4
Order By: Relevance
“…They observed that the increase in leftward asymmetry was linearly correlated with age but also, independently of age, with verbal performances. Importantly, in the same individuals they measured hemispheric asymmetries during a visuospatial task and observed the reverse pattern for this right hemisphere-dominant function: a right asymmetry increase with age, and the larger the rightward asymmetry, the better the visuospatial performances of the participants (Everts et al 2009). …”
Section: Cognitive Skills and Asymmetriesmentioning
confidence: 91%
See 1 more Smart Citation
“…They observed that the increase in leftward asymmetry was linearly correlated with age but also, independently of age, with verbal performances. Importantly, in the same individuals they measured hemispheric asymmetries during a visuospatial task and observed the reverse pattern for this right hemisphere-dominant function: a right asymmetry increase with age, and the larger the rightward asymmetry, the better the visuospatial performances of the participants (Everts et al 2009). …”
Section: Cognitive Skills and Asymmetriesmentioning
confidence: 91%
“…Everts et al (2009) mapped 9-21-year-old healthy participants during rhyming and synonym language tasks and measured both their hemispheric asymmetry and their verbal abilities. They observed that the increase in leftward asymmetry was linearly correlated with age but also, independently of age, with verbal performances.…”
Section: Cognitive Skills and Asymmetriesmentioning
confidence: 99%
“…The vowel detection task is a well-established fMRI-based method for detecting the neural network of internal word generation and phonological detection (Everts et al, 2009;Wilke et al, 2006). The task is known to reliably activate inferior frontal and superior temporal regions in children aged 6 to 16 years (Everts et al, 2009;Wilke et al, 2006).…”
Section: Fmri Assessmentmentioning
confidence: 99%
“…Structural alterations can influence cognitive outcome. Carreiras et al (2009) found that a smaller volume of the increase in language lateralization to the left hemisphere with increasing age, which is likely associated with higher Verbal-IQ (Everts et al, 2009;Holland et al, 2001;Holland et al, 2007). In very preterm born children, studies suggest alternative neural language organization: 12-year-old very preterm born children showed a more extended auditory processing network during a passive listening task when compared with a control group (Ment et al, 2006).…”
mentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies have demonstrated that left hemisphere dominance of language function may already be present in infants Ïœ1 year old (Dehaene-Lambertz et al, 2002;Peña et al, 2003). In older children (ÏŸ5 years old), not only left-lateralized responses during language-related tasks (Balsamo et al, 2002;Ahmad et al, 2003), but also correlations between brain functional lateralization and language performance (Everts et al, 2009) have been reported. Previous fMRI studies, however, did not concentrate on the link between language performance and brain functional lateralization in healthy preschool children aged 1-4 years old, because this is a challenging age for brain imaging methods such as fMRI.…”
Section: Introductionmentioning
confidence: 99%